Activity of Madden Julian Oscillation during 2002 and 2006 – A comparative analysis (MAUSAM, 2008)
The Indian summer monsoon is characterized by very significant intra-seasonal variability. Madden-Julian Oscillation (MJO) is one of the dominant modes of the intra-seasonal variability of the Indian summer monsoon rainfall.  The activity of Madden Julian Oscillation during the monsoon seasons of the two years of contrasting intra-seasonal rainfall variability has been examined in terms of rainfall activity over India and eastward propagation of convection in the near-equatorial region. The study shows the contrasting nature, viz., in the monsoon season of 2002, eastward mode dominated whereas in 2006, it remained suppressed.